2010
DOI: 10.2105/ajph.2009.163089
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Emotional, Physical, Sexual, and Financial Abuse and Potential Neglect in the United States: The National Elder Mistreatment Study

Abstract: Objectives. We estimated prevalence and assessed correlates of emotional, physical, sexual, and financial mistreatment and potential neglect (defined as an identified need for assistance that no one was actively addressing) of adults aged 60 years or older in a randomly selected national sample. Methods. We compiled a representative sample by random digit dialing across geographic strata. We used computer-assisted telephone interviewing to standardize collection of demographic, risk factor, and mistreatment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

57
825
13
30

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,128 publications
(925 citation statements)
references
References 12 publications
57
825
13
30
Order By: Relevance
“…4 A study conducted in Spain demonstrated reported the following types of violence: emotional (4.6%); physical (1.6%); sexual (0.6%); and financial (5.6%). 5 In Nigeria, 30% of the elderly participants in a study claimed to have suffered from some form of violence. 6 In Brazil, a study conducted in the city of Niterói investigated the prevalence of violence against individuals aged 60 years or more, confirming that 43% of this aggression was psychological and 9.6% was physical.…”
Section: Introductionmentioning
confidence: 99%
“…4 A study conducted in Spain demonstrated reported the following types of violence: emotional (4.6%); physical (1.6%); sexual (0.6%); and financial (5.6%). 5 In Nigeria, 30% of the elderly participants in a study claimed to have suffered from some form of violence. 6 In Brazil, a study conducted in the city of Niterói investigated the prevalence of violence against individuals aged 60 years or more, confirming that 43% of this aggression was psychological and 9.6% was physical.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Some factors may increase the risk of aggression, such as a lack of financial resources, previous experience of violent events among family members, drug abuse, mental health problems and high levels of stress. 10 The scarcity of information regarding these cases should be noted. This is primarily as a result of the reluctance of elderly individuals to report abuse and aggression, because of embarrassment and fear of repression from caregivers, who are commonly themselves the aggressors.…”
Section: Introductionmentioning
confidence: 99%
“…24 No. 5, 2012 467 지역사회에 거주하는 노인 뇌졸중 환자의 학대 관련 요인 는 잠재적 방임 상태를 경험하고 있는 것으로 나타났다 (Acierno et al, 2010).…”
unclassified